Development of wet adhesion of honeybee arolium incorporated polygonal structure with three-phase composite interfaces - Lulu Liang; Jieliang Zhao; Qun Niu; Li Yu; Xiangbing Wu; Wenzhong Wang; Shaoze Yan; Zhenglei Yu (Friction)
Abstract Inspired by the dynamic wet adhesive systems in nature, various artificial adhesive surfaces have been developed but still face different challenges. Crucially, the theoretical mechanics of wet adhesives has never been sufficiently revealed. Here, we develop a novel adhesive mechanism for governing wet adhesion and investigate the biological models of honeybee arolium for reproducing the natural wet adhesive systems. Micro-nano structures of honeybee arolium and arolium-prints were observed by Cryogenic scanning electron microscopy (Cryo-SEM), and the air pockets were found in the contact interface notably. Subsequently, the adhesive models with a three-phase composite interface (including air pockets, liquid secretion, and hexagonal frames of arolium), were formed to analyze the wet adhesion of honeybee arolium. The results of theoretical calculations and experiments indicated an enhanced adhesive mechanism of the honeybee by liquid self-sucking effects and air-embolism effects. Under these effects, normal and shear adhesion can be adjusted by controlling the proportion of liquid secretion and air pockets in the contact zone. Notably, the air-embolism effects contribute to the optimal coupling of smaller normal adhesion with greater shear adhesion, which is beneficial for the high stride frequency of honeybees. These works can provide a fresh perspective on the development of bio-inspired wet adhesive surfaces.